ANTI DIABETIC AND CYTOTOXIC POTENTIAL USING METHANOLIC CRUDE EXTRACT PREPARATION FROM SARGASSUM WIGHTII SEAWEED - Mounithaa N, Dr. Abirami Arthanari, Dr. Sivaperumal.P, (Chelonian Research Foundation, 2023)
Introduction: Our study explores the potential of using Sargassum wightii seaweed as a source for alternative fuels due to its rich composition of bioactive compounds. The seaweed, belonging to the brown algae category, is widely distributed in tropical and temperate environments. Extracts from these seaweeds can be processed into a third-generation biofuel, surpassing land biomass techniques in efficiency. Aim: The primary objective is to evaluate the anti-diabetic and cytotoxic potential of methanolic crude extract derived from Sargassum wightii seaweed. Additionally, the research aims to understand the bioactive composition of the seaweed and its suitability for biofuel production. Materials and methods: Sargassum wightii samples were collected and washed thoroughly , the seaweed was shade-dried, powdered, and subjected to methanolic extraction. The crude extract underwent concentration and was stored for subsequent analysis. Preliminary phytochemical screening tests were conducted to identify bioactive compounds. In vitro tests, including α-amylase and α-glucosidase inhibition assays, assessed the anti-diabetic potential. Cytotoxicity was evaluated using MTT assays on breast cancer cells. A GC-MS analysis was performed to identify the chemical composition of the seaweed extract. Results: The study revealed significant anti-diabetic activity, with the extract inhibiting α-amylase and α-glucosidase enzymes. Cytotoxicity assays demonstrated a dose-dependent reduction in breast cancer cell viability. GC-MS analysis identified various bioactive compounds in the seaweed extract, including fucoxanthin. Conclusion: Sargassum wightii exhibits promising anti-diabetic and cytotoxic properties, validating its potential as a natural source for pharmaceutical applications. The presence of bioactive compounds underscores its significance in biofuel production. Further investigations are warranted to isolate specific active compounds and advance understanding for potential clinical applications in diabetes management and cancer treatment. Keywords:Sargassum wightii,alternative fuels, anti-diabetic, cytotoxic, bioactive compounds, biofuel, seaweed extract, pharmaceutical applications, diabetes management, cancer treatment.